CONSTRUCTION OF A SCHOOL WEBSITE AS AN INFORMATION SYSTEM SOLUTION AT MTS NURUL HUDA, PANGGUNG TANGGAMUS ISLAND LAMPUNG - Saputra, Ricco Herdiyan; Novitasari, Dita; Waziana, Winia (Universitas Islam Negeri Raden Intan Lampung, 2024)
The fact that Madrasah Tsanawiyah Nurul Huda Tekad Pulau Panggung District only distributes brochures throughout the Pulau Panggung District and its environs has a significant influence on the admission of new students, as only potential students who receive the brochure are aware of MTS Nurul Huda. As a result, the school has not yet expanded its information dissemination efforts. A website-based information system that can assist in distributing information to potential students is adopted to ensure that information is sent appropriately. To facilitate information access for administrators, instructors, and the general public via the school website, this study intends to develop a website-based information system at MTS Nurul Huda School. The waterfall problem-solving approach will be employed in this study, and data will be gathered via literature review, interviews, and observation. In addition to the presence of a PPDB feature that can facilitate prospective students' access to the registration form at MTS Nurul Huda via the website, this web-based information system has the potential to reduce the management and provision of academic information, including school profiles, school history, vision, and mission.